2004
DOI: 10.1111/j.1439-0434.2004.00915.x
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Molecular Characterization of Viruses Infecting Cucurbits in Pakistan

Abstract: Cucurbits are grown throughout the North-West Frontier Province of Pakistan as summer and winter crops. Plants having mosaic, mottling, chlorosis and leaf distortion symptoms were frequently found in most of the cucurbit fields during the survey. Using dot immunobinding assay, Cucumber green mottle mosaic virus (CGMMV), Zucchini yellow mosaic virus (ZYMV), Watermelon mosaic virus (WMV) and Papaya ringspot virus (PRSV) were found infecting cucurbits. CGMMV was widespread, infecting 46.9% of the samples tested f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
43
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 58 publications
(45 citation statements)
references
References 14 publications
2
43
0
Order By: Relevance
“…The stability of the mild strain in this case should not be a concern as tobamoviruses are known to have the most stable genome among the plant viruses, but one must always need to take the necessary precautions by continually evaluating the actual inocula used for crossprotection. Although, the previous findings Ali et al, [24] indicate very low level of diversity in the sequence of CGMMV isolates reported so far, one must also investigate the diversity of the virus in the area concerned. Some sort of variability do occur in genome of CGMMV, which is also reflected by different symptom expressions reported for watermelon isolate from Japan and CGMMV-Pk.…”
Section: Discussionmentioning
confidence: 94%
See 4 more Smart Citations
“…The stability of the mild strain in this case should not be a concern as tobamoviruses are known to have the most stable genome among the plant viruses, but one must always need to take the necessary precautions by continually evaluating the actual inocula used for crossprotection. Although, the previous findings Ali et al, [24] indicate very low level of diversity in the sequence of CGMMV isolates reported so far, one must also investigate the diversity of the virus in the area concerned. Some sort of variability do occur in genome of CGMMV, which is also reflected by different symptom expressions reported for watermelon isolate from Japan and CGMMV-Pk.…”
Section: Discussionmentioning
confidence: 94%
“…Five viruses were found infecting the crops, with CGMMV being the most widespread [24]. The dominance of CGMMV could be attributed to the contact transmission of the virus, coupled with the poor phytosanitary measures.…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations